Parent-led strategies supporting personal well-being when caring for a child with a life-limiting condition: A scoping review. (December 2022) - Oakley, Sarah; Dunbar, Helena; de Vries, Kay
The objectives of this review were to identify strategies initiated by parents of children with life-limiting conditions to support their own well-being at home and to describe the impact of these strategies on parental well-being. A systematic scoping review was performed using PRISMA-ScR guidelines, identifying 15 relevant studies that fit the inclusion and exclusion criteria. There were no studies that specifically assessed how parents support their own well-being; however, the 15 identified studies did provide pertinent data secondary to the primary aims of each study. This resulted in the identification of 14 parent-initiated strategies which were grouped thematically into 4 categories: (i) social experience and peer support, (ii) information and management techniques, (iii) reframed perspectives and (iv) prioritising own needs. Overall, there was some evidence of parents initiating specific, individualised and useful strategies to supporting their well-being. Notably lacking was any empirical evaluation as to the effectiveness of these strategies and the wider factors associated with them. Further research is required to assess how parents support their personal well-being in daily life and how these strategies can be implemented alongside service-initiated support to ensure full parental well-being.